The emperor's caretaker. 4 - Hiiragi, Ichiha (Square-Enix Manga & Books, 2025)
Linhua is secretly engaged to Prince Souren, the most breathtaking man in all of Guangyan-but their relationship must stay hidden until Emperor Zhiyou comes of age. Trouble brews when the new Chancellor of the Left, Lee Songhua, sets his sights on Linhua, sparking a confrontation with Souren. Meanwhile, the stage is set for a new era as the selection of Emperor Zhiyou's inner circle begins!